TINJAUAN ARTIKEL: PEMASANGAN DENTAL IMPAN SETELAH ELEVASI LANTAI SINUS DENGAN TEKNIK OSTEOTOMI - Halim, Susanna; Muharraran, Firdha; Aulia, Dinda Rizky; Kartika, Disya Citta; Selvina, Weni (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Dental implant is considered the optimal rehabilitation option for tooth loss, a prevalent issue in Indonesia that can impair oral function. However, it presents technical challenges, particularly in the posterior maxilla where bone volume is limited. This study constitutes a literature review conducted using Google Scholar and Science Direct databases, spanning the years 2000–2024, with the keywords